Net neutrality and investment incentives - Jay Pil Choi; Byung-Cheol Kim (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes the effects of net neutrality regulation on investment incentives for Internet service providers (ISPs) and content providers (CPs), and their implications for social welfare. We show that the ISP's decision on the introduction of discrimination across content depends on a potential trade-off between network access fee and the revenue from the trade of the first-priority. Concerning the ISP's investment incentives, we find that capacity expansion affects the sale price of the priority right under the discriminatory regime. Because the relative merit of the first priority, and thus its value, becomes relatively small for higher capacity levels, the ISP's incentive to invest on capacity under a discriminatory network can be smaller than that under a neutral regime where such rent extraction effects do not exist. Contrary to ISPs' claims that net neutrality regulations would have a chilling effect on their incentive to invest, we cannot dismiss the possibility of the opposite.
Keywords: D4; L12; L4; L43; L51; L52; 330; Net neutrality; investment (innovation) incentives; queuing theory; hold-up problem; two-sided markets; vertical integration; Netzzugang; Service Provider; Online-Dienst; Investition; Ökonomischer Anreiz; Vertikale Konzentration; Theorie; Theorie